2002
DOI: 10.1530/eje.0.1470065
|View full text |Cite
|
Sign up to set email alerts
|

Plasma ghrelin levels during exercise in healthy subjects and in growth hormone-deficient patients

Abstract: Objective: To characterise plasma levels of the recently identified endogenous ligand for the GH secretagogue receptor (ghrelin) during submaximal aerobic exercise in healthy adults and in GH-deficient adults. Design: Eight healthy males (mean^S.E. age, 40:8^2:9 years) and eight hypopituitary males with verified GH deficiency (mean^S.E. age, 40:8^4:7 years) underwent a baseline test of their peak aerobic capacity (VO 2 peak) and lactate threshold (LT) on a cycle ergometer, as well as an evaluation of body comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

12
86
6
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(105 citation statements)
references
References 20 publications
(31 reference statements)
12
86
6
1
Order By: Relevance
“…In humans, exercise has been reported not to influence plasma ghrelin levels even at high exercise intensities [28][29][30]. We are unaware of other published data in which the plasma ghrelin response to exercise has been studied in rats.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, exercise has been reported not to influence plasma ghrelin levels even at high exercise intensities [28][29][30]. We are unaware of other published data in which the plasma ghrelin response to exercise has been studied in rats.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of studies have focused on aerobic (cardiovascular) exercise (31), with only three studies examining the effects of resistance (muscle strengthening) exercise, and these have reported contradictory effects (21,33,47). Resistance exercise is a key component of exercise recommendations for weight control (2) and public health (23, 42); thus, it is important to clarify the effects of resistance exercise on hunger and gut hormones.The effect of acute exercise bouts on total plasma ghrelin concentrations is controversial, with studies reporting no changes either during or postexercise (10,15,26,27,32,39,43,45,47), as well as increases (14,17,25,44) and decreases (21,33,48,50). Acylation of ghrelin is thought to be essential for appetite regulation because only the acylated form of the hormone can cross the blood-brain barrier (41).…”
mentioning
confidence: 99%
“…Pubertal GH surge is not associated with ghrelin levels [27]. Furthermore, GH pulsatility is not explained by changes in ghrelin concentration [43] and acute GH response in exercise is not associated with the changes in ghrelin levels [25,31]. Interestingly, ghrelin-deficient mice are viable and exhibit a normal growth rate, demonstrating that ghrelin is not critical for normal growth [23].…”
Section: Discussionmentioning
confidence: 99%
“…Even though IGF-I is not universally regarded as an ideal discriminator of GH status [44], IGF-I measurement is currently the best indirect method to assess GH secretion [45]. The recent studies have reported negative association between ghrelin and IGF-I concentrations in children and adolescents [27][28][29][30] whereas nihilistic results has been reported in adult subjects [31][32][33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation